CDKN1A as a target of senescence in heart failure: insights from a multiomics study - Bian, Rutao; Zhang, Li; Li, Dongyu; Xu, Xuegong (Frontiers in Pharmacology, 2024)
Cardiomyocyte senescence plays a crucial role as a pathological mechanism in heart failure (HF). However, the exact triggering factors and underlying causes of HF onset and progression are still not fully understood.By integrating multi-omics data, this study aimed to determine the genetic associations between cardiomyocyte and HF using cell senescence-related genes (SRGs).The study utilized the CellAge database and the SenMayo dataset, combined with high-resolution single-cell RNA sequencing (scRNA-seq) data, to identify SRG and examine differences in cardiac cell expression. To explore the causal relationship with HF using Mendelian Randomization (MR). Genetic variations influencing gene expression, DNA methylation, and protein expression (cis-eQTL, cis-mQTL, and cis-pQTL) were analyzed using the two-sample MR (TSMR) and summary-data-based MR (SMR). Additionally, Bayesian colocalization analysis, germline genetic variation, and bulk RNA data were employed to strengthen the reliability of the results. The application potential of therapeutic targets is ultimately assessed by evaluating their druggability.The expression of 39 SRGs in cardiomyocytes was identified. In the discovery set revealed that CDKN1A (OR = 1.09, 95% confidence interval (CI) 1.02-1.15, FDR = 0.048) could be causally related to HF, and the results are also replicated in the validation set (OR = 1.20, 95% confidence interval (CI) 1.10-1.30, FDR < 0.0001).Based on the SMR method, CDKN1A was confirmed as a candidate pathogenic gene for HF, and its methylation (cg03714916, cg08179530) was associated with HF risk loci. The result is validated by Bayesian colocalization analysis, genetic variations, and bulk RNA data. The druggability analysis identified two potential therapeutic drugs.Based on multi-omics data, this study uncovered the reciprocal regulation of cardiomyocyte senescence through CDKN1A, providing potential targets for HF drug development.